A Single gD Glycoprotein Can Mediate Infection by Herpes simplex Virus - Clarke, Richard W. (American Chemical Society, 2013)
[Image: see text] Herpes simplex viruses display hundreds of gD glycoproteins, and yet their neutralization requires tens of thousands of antibodies per virion, leading us to ask whether a wild-type virion with just a single free gD is still infective. By quantitative analysis of fluorescently labeled virus particles and virus neutralization assays, we show that entry of a wild-type HSV virion to a cell does indeed require just one or two of the approximately 300 gD glycoproteins to be left unbound by monoclonal antibody. This indicates that HSV entry is an extraordinarily efficient process, functioning at the level of single molecular complexes.